ANALISIS DAMPAK PERMUKIMAN KUMUH TERHADAP KAWASAN PESISIR KELURAHAN TALLO - Mega Ambriliani Robichin; Andi Tamsil; St Hadijah (JURNAL AKUAKULTUR, TEKNOLOGI DAN MANAJEMEN PERIKANAN TANGKAP, ILMU KELAUTAN, 2019)
The existence of slums in the coastal area has an impact on decreasing environmental quality both in the environment itself and the surrounding environment. This study aims to find out and analyze the factors that influence the impact of slums on the coastal areas of Tallo Village and the concepts and strategies of handling in an effort to minimize the impact. The study used a questionnaire on 133 samples, interviews and object documentation as instruments for primary data collection and literature and institutional studies for secondary data collection. The analytical tool used is multiple linear regression analysis, SWOT analysis and deskiptif analysis. The results of the analysis show the factors that influence the impact of slums on the coastal areas of Tallo Village, namely environmental factors, social factors and economic factors. The concept of handling slums in the coastal area of Tallo Village, namely 1). Prevention concepts (supervision, control & community empowerment) and 2). The concept of improving the quality of the environment (renewal & new development)